2019
DOI: 10.1093/mnras/stz2317
|View full text |Cite
|
Sign up to set email alerts
|

Gaia parallax of Milky Way globular clusters – A solution of mixture model

Abstract: We have established a mixture model approach to derive the parallax of the Milky Way globular clusters. It avoids the problem of cluster membership determination and provides a completely independent astrometrical solution by purely using the parallax data. This method is validated with simulated clusters of Pancino et al. (2017). We have resolved 120 real globular clusters by the mixture model using parallaxes of the second data release of Gaia . They construct the largest direct parallax sample up to now. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
(33 reference statements)
4
9
0
Order By: Relevance
“…Using Gaia parallaxes, Chen et al (2018) obtained a distance of 4.45 kpc ± 0.01 (random) ± 0.12 (systematic) to 47 Tuc (we note that the recent paper by Shao & Li (2019) has not improved on their results).…”
Section: Distance Estimatementioning
confidence: 80%
“…Using Gaia parallaxes, Chen et al (2018) obtained a distance of 4.45 kpc ± 0.01 (random) ± 0.12 (systematic) to 47 Tuc (we note that the recent paper by Shao & Li (2019) has not improved on their results).…”
Section: Distance Estimatementioning
confidence: 80%
“…The strategy of our approach is using the mixture model method, which is a natural statistical method for many situations in astronomy (Kuhn & Feigelson 2017). It is verified that even in a heavily mixed case, like the parallax distributions of field stars and members of distant globular clusters (Shao & Li 2019), the mixture model method can also fit the distribution parameters precisely.…”
Section: Model and Algorithmmentioning
confidence: 89%
“…The DR2 offset was calibrated from quasars, which are bluer than the bulk of ω Cen stars and only cover a small fraction of their magnitude range. The DR2 parallax estimates for ω Cen by Gaia Collaboration et al (2018a) and by Shao & Li (2019) are 0.1237 ± 0.0011 and 0.1368 ± 0.0015 mas, respectively, and are substantially smaller than other determinations, presumably because the parallax offset estimated by Lindegren et al (2018) on the basis of quasar data is much smaller than the values found for brighter stars (Riess et al 2018;Arenou et al 2018;Zinn et al 2019). Our own analysis of the DR2 parallax data for stars in ω Cen revealed a large trend of parallax with star magnitude and color, leaving us to conclude that a parallax from DR2 was not reliable without further characterization of its parallax offset.…”
Section: Comparison With Prior Distance Measurements For ω Cenmentioning
confidence: 94%